STUDY OF AMINO ACID COMPOSITION OF SILK AND WOOL FABRIC - Erkinov Jamshidbek Dilshodbek o’g’li (Zeta Repository, 2023)
Research has been carried out to determine the amino acid composition of wool and silk. On the basis of IR spectrometry, connections have been shown that have an essential role in the structure of proteins.